DEVELOPMENT OF A SIMULATION MODEL OF OPERATION MODES OF MICRO-HYDROELECTRIC POWER PLANTS - Sirojdin Fayozovich Ergashev; Abdulazizov Sanjar Solijon o'g'li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In this state, with the use of the MATLAB Simulink modeling package, a model of the system of autonomous electrical supply of the village house with a power of 3 kW based on the micro-hydroelectric power plant is developed. A series of experiments was carried out using MATLAB software. And as a result of the experiments, the system electrical power supply system was studied and determined by different modes of operation.